2007
DOI: 10.1200/jco.2007.12.2440
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Plus Irinotecan in Recurrent Glioblastoma Multiforme

Abstract: Bevacizumab and irinotecan is an effective treatment for recurrent glioblastoma multiforme and has moderate toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
803
11
14

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,273 publications
(863 citation statements)
references
References 30 publications
35
803
11
14
Order By: Relevance
“…In the latter study, patients who had received temozolomide as a first-line therapy benefited from a dose-intensified re-exposure, too. Another phase II study evaluated the use of bevacizumab, a monoclonal antibody to vascular endothelial growth factor, in combination with irinotecan, a topoisomerase inhibitor [18,19]. This study reached a PFS-6 of 46% in patients with recurrent glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, patients who had received temozolomide as a first-line therapy benefited from a dose-intensified re-exposure, too. Another phase II study evaluated the use of bevacizumab, a monoclonal antibody to vascular endothelial growth factor, in combination with irinotecan, a topoisomerase inhibitor [18,19]. This study reached a PFS-6 of 46% in patients with recurrent glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, no direct comparisons are available and the trials evaluating bevacizumab plus temozolomide were conducted in part in highly pretreated patient populations [72][73][74]. Five phase II trials evaluated the combination of irinotecan with bevacizumab [91][92][93][94][95], two trials added a third combination partner, cetuximab [96] or carboplatin [97]. PFS-6 rates ranged between 28 and 50.3% and median OS between 6.7 and 9.7 months.…”
Section: Bevacizumab Monotherapy and Combination Regimensmentioning
confidence: 99%
“…A prospective phase 2 study using every-3-week dosing of bevacizumab at a dose of 15 mg/kg in 61 patients with World Health Organization grade 3 or grade 4 glioma demonstrated no obvious differences in patient outcomes compared with contemporary studies using every-2-week dosing at 10 mg/kg, 37 thus allowing for flexibility in patient scheduling without clinical detriment. Several phase 2 trials of bevacizumab-based combinations have also been reported for recurrent glioblastoma (Table 1), 27,28,32, including bevacizumab with irinotecan, irinotecan plus cetuximab, irinotecan plus carboplatin, etoposide, fotemustine, sorafenib, temozolomide, erlotinib, and temsirolimus. 27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide.…”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%
“…Several phase 2 trials of bevacizumab-based combinations have also been reported for recurrent glioblastoma (Table 1), 27,28,32, including bevacizumab with irinotecan, irinotecan plus cetuximab, irinotecan plus carboplatin, etoposide, fotemustine, sorafenib, temozolomide, erlotinib, and temsirolimus. 27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide. [48][49][50][51][52][53][54][55][56][57][58] Although these small studies are not easily compared due to their size and various patient populations, the consensus to date has been that no combination significantly surpasses the outcomes of bevacizumab monotherapy for recurrent glioma.…”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%